Communication satisfaction among academic staff in Malaysian public universities - Sadia, Aysha; Mohd Salleh, Berhannudin; Abdul Kadir, Zulida; Sanif, Sazuliana (Econjournals, 2017)
Communication satisfaction is of dominant position in any organization as it contributes to the effectiveness and success of an organization. The communication satisfaction of an organization may affect the atmosphere in the organization which either encourages or hinders horizontal, upward or downward communication among the employees. In organizations with defensive climates, employees have the tendency to abstain from communicating their needs, as they become very cautious in making statements, and may have low level of motivation. Organizations with understanding atmospheres inspire active participation, healthy exchange of information and constructive problems resolves. The objective of the present study is to investigate the major hindrances and problems of communication satisfaction among academic staff of Malaysian public universities and its impact on management function and organizational communication. This study is expected to investigate communication satisfaction among academics with supervisory role in the respective university. It aims to determine the patterns of communication system in universities, to analyze various challenges to the communication and to suggest ways of improving communication system. This research study would foster the knowledge and understanding of improving of communication satisfaction in academic organizations particularly tertiary institutions and would help improve productivity and harmonious working environment adopt better process and programs in order to overcome.